Efforts by top travel destinations to manage and mitigate overtourism and touristification: Case of study (Venice, Italy Barcelona, Spain Bali, Indonesia Santorini, Greece) - Nadjat, Benzayed; Bilal, Bekhouche (The International tax journal, 2025)
This study explores the proactive measures adopted by top tourist destinations to manage and mitigate the negative impacts of overtourism and touristification, using Venice, Italy Barcelona, Spain Bali, Indonesia Santorini, Greece, as a case study. Based on statistical analysis theory, the analysis focuses on the economic, social and regional dynamics that influence the expansion of suspicious transaction reports and their contribution to rural tourism. By applying spatial and temporal indicators, the study identifies areas where suspicious transaction reports have intensified pressures on land use, housing and community life. The findings underscore the importance of coordinated planning policies and sustainable tourism strategies to address the uncontrolled spread of suspicious transaction reports, reduce housing market distortions, and protect rural environments. The case of Mallorca illustrates how local and national authorities have begun to adopt targeted regulations to control tourism flows and ensure that residents benefit from the development and long-term sustainability of the destination.